Dynamic and Precise Engineering Surveying - Li, Qingquan (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
Driven by the increasingly expanding needs of infrastructure construction, operation and maintenance, as well as the rapid developments of intelligent sensing and information technology, precise engineering surveying has been transformed from static, discrete, and manual into dynamic, continuous, and intelligent ways. This transformation leads to an advanced multidisciplinary field, dynamic and precise engineering surveying, on which the author has worked for over two decades. This book systematically summarizes the fundamentals, methods, and applications in dynamic and precise engineering surveying. The contents mainly include two parts: the first part introduces principles and methods of dynamic and precise engineering surveying; the second part presents representative applications in which innovative methods and advanced equipment are applied in the construction, operation and maintenance of mega and complex infrastructures. Readers engaged in surveying and mapping, civil engineering, water conservancy engineering, railway engineering, electronic information, and computer science, including undergraduates, graduates, researchers and engineers, will find it an informative reference.
Introduction -- Structural state surveying for transportation infrastructure -- Dynamic surveying in autonomous driving -- Indoor and underground space measurement -- UAV 3D measurement -- Coastal zone survey -- Outlook. .
Keywords: Geographic information systems; Surveying; Cartography; Geotechnical engineering; Geographical Information System; Surveying; Cartography; Geotechnical Engineering and Applied Earth Sciences